Plastic deformation in asphalt layers: laboratory evaluation - Castro, Pedro (2025)
Plastic deformation in asphalt concrete layers is one of the most common modes of distress in flexible pavement structures in the Costa Rican context. This phenomenon is related to the compressibility of the layer (consolidation under loads) and/or the lack of shear strength (plastic flow).